WITH THE APPEARANCE OF COVID-19 THE DETERMINATION OF THE „FINISHED” ICE HOCKEY CHAMPIONSHIPS’ FINAL RESULTS – FROM THE POINT OF VIEW OF THE THEORIES OF JUSTICE - Zimányi, Róbert G. (Stadium - Hungarian Journal of Sport Sciences, 2021)
COVID-19 has long-term effects – solving (or trying to solve) these primary social problems attention can also be focused on sport as a social subsystem. The study examines the competitive sport, including the final results of championships in ice hockey. Most championships were going on when the COVID-19 pandemic broke out. As a result, the most of the championships were suspended – which were either continued after the restrictions, or ended the season. What about the ice hockey tournaments, where the season ended prematurely? In this case, was the final result determined as well? If so, on what basis? At determining the final results, the organizers tried to make the most just decision. However, on what basis is it just to determine the final results of these championships? The study examines several theories of justice which play a (key) role in determining the final result of ice hockey in different championships. The study confirms this theory in several case examples: the organizers (league association) really made a just decision. The only, but the most important question is: which theory of justice was (or theories of justice were) dominated in determining the final results? In each case examined, the principle of meritocracy appeared (at some level). In accordance to the nature (telos) of the competitive sports, at determining of the final results the idea of meritocracy dominated. However, there is also a difference within meritocracy: between the timeliness and actuality of the reached results. In addition to the achievements on the sports field, the egalitarianism has also appeared in many cases, as another theory of justice – as well as the utilitarianism (by Bentham and Mill).